The Systematic Procurement: Educational Supply Chain Management System - Kyaw Zay Ya; Fahmi Rizal; Anugrah Agung Ramadhan (Program Studi S3 Ilmu Manajemen, 2021)
Procurement is one of the functions involving in the Educational Supply Chain. It is highly important for teaching-learning process, more specifically Engineering programs that are comprised with practical teaching and theory teaching. For practical teaching, the supplies of equipment, facilities, tools and learning materials are dependent on the systematic procurement. This study is aimed to discover the procurement system of the Engineering Faculty, Universitas Negeri Padang, as a single case study. This is the qualitative research which uses semi-structured interview. Thirteen academicians and thirty five management practitioners were interviewed to gain in-depth information about the procurement existing in the case faculty. Purposive sampling method and simple random sampling method were used to select the research subjects. O'Connor & Gibson (2003)’s step-by-step qualitative analysis method was employed to analyze the data. The study resulted the regular procurement system and urgent procurement system in the faculty.